Problem aspects of transformation in financial reporting of business entities in Ukraine - Fedir Zhuravka (Geopolitics under Globalization)
In many countries International Financial Reporting Standards (IFRS) have become part of the domestic law or common practice. Ukraine has also taken the first steps to the use of IFRS taking into account its national peculiarities. However, problems occur in the adaptation of international standards, which need to be solved. The proposed article is devoted to the research of specific problems arising during the implementation of IFRS in Ukraine. The author substantiates the expediency of implementing International Financial Reporting Standards in Ukraine, studies the prospects of using international standards in the national accounting practices and defines the principle of transformation as a priority. It determines the stages of IFRS implementation in Ukraine and the problems that arise on each of these stages. As a result, the study highlights the shortcomings of the national accounting system’s reform and ways of optimizing the process of IFRS implementation in Ukraine.